Risk Factors for Second Litter Syndrome in Landrace × Yorkshire Sows in Tropical Conditions - Nam, N. H.; Lanh, D. T. K.; Thanh, N. V.; Dung, B. V.; Dao, B. T. A.; Sukon, P. (Tropical Animal Science Journal, 2025)
Second litter syndrome (SLS), defined as an equal or lower number of piglets born alive (NBA) in the second parity compared to that in the first, is a major reproductive concern in commercial sow herds worldwide. This study aimed to identify factors associated with SLS under tropical conditions in Vietnam. Data from 3,957 Landrace × Yorkshire sows farrowing the second litter between 2024 and 2025 were analyzed using logistic regression. The overall incidence of SLS was 56.8%, with mean NBA of 12.7 in both parities. In the multivariable model 1, NBA in the first parity (NBA1) was the strongest predictor, accounting for 50.3% of the explained variation (OR=2.3, 95% CI: 2.2-2.4, p470 days. Model 2, excluding NBA1, identified additional risk factors, including litter size at weaning (LSW), weaning-to-service interval (WSI), and month of insemination after the first weaning. Sows that weaned >14 piglets had threefold higher odds of SLS compared to those weaning fewer than 11 piglets (p17 days (p